Evaluating the impact of precision -guided munitions on human suffering in war, 1967-1999: An ethics-based approach - Hickey, James E (ProQuest Dissertations & Theses, 2009)
Throughout history, humans have demonstrated a proclivity for using violence against one another as a means to achieve an end, means enabled, in many respects, by the technologies available at the time. For much of that history, advancing technology has been a prime enabler of ever- increasing levels of violence and attendant human suffering. However, at a few junctures in history, certain technologies have seemingly provided the armed forces that possess them the ability to fight wars with decreasing levels of violence and suffering. In the seventeenth century, for example, such hopes, later unrealized, were held for gunpowder and artillery. Today, precision-guided munitions (PGMs) with their high degree of discrimination and accuracy again hold such promise. This multidisciplinary study, integrating ethics, history, religion, and philosophy seeks to answer the question: Do PGMs mitigate suffering in war, and have these weapons changed the way decisions regarding war and peace have been made? To do so, it develops a three-part evaluative framework that combines core principles of the Just War Tradition with concerns about technology expressed by the French philosopher Jacques Ellul. The framework first examines the impact that PGMs have on human suffering during a conflict, and then extends that analysis forward by examining the future implications caused by unintended consequences. The final part of the framework examines the influence of PGM capability on national leaders' decision-making when considering using violence. Across four case studies, comprising eleven times when military force was used as a tool of national power, the study concludes that, between 1967 and 1999, PGMs have indeed had a positive impact on reducing human suffering in war.